Biaya Disfungsional dalam Sistem Kontrol Manajemen: Tinjauan Teoretis dan Implikasi - Salma Arobani; Eri Kusnanto (Jurnal Bisnis Kreatif dan Inovatif, 2025)
This qualitative literature review examines the dysfunctional costs that emerge within Management Control Systems (MCS), a critical organizational mechanism designed to align employee behavior with strategic objectives. Although prior studies have extensively explored the benefits of control systems, discussions on the unintended and often hidden costs remain fragmented. This article aims to synthesize theoretical insights and conceptual debates surrounding four major categories of dysfunctional costs: behavioral displacement, game-playing, operating delays, and negative attitudes. Using a traditional literature review approach, the study integrates foundational theories including agency theory, behavioral control theory, and goal-setting theory with contemporary conceptual findings to identify key behavioral mechanisms that trigger dysfunctional outcomes. The review reveals that overly rigid controls, inappropriate performance targets, and misaligned incentives frequently prompt short-termism, budget slack, manipulation, bureaucratic delays, and psychological strain among employees. These dysfunctional costs can surpass direct control costs and reduce organizational adaptability and long-term performance. The study highlights the need for context-sensitive control design, balanced use of results and action controls, and enhanced attention to behavioral responses when implementing MCS. The implications underscore that effective control is achieved not through tighter rules alone but through thoughtful alignment between control mechanisms, human behavior, and organizational context.